Pendampingan Pencegahan Penyakit Akibat Kerja pada Pekerja Bagian Produksi Furniture CV Rumah Menyala di Desa Tegalsari, Kecamatan Kandeman, Kabupaten Batang - Mastuti, Dewi Nugraheni Restu; Maulana, Jaya; Irawan, Teguh; Hermawan, Agung; Navisa, Dita khafka; Aulia, Mahda Ridhotul; Aprilia; Febriliyanti, Imelia; ‘Amali, M Shodiqul (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Every workplace, both formal and informal, has various potential hazards that can affect the health of workers or can cause occupational diseases. In the furniture industry, workers are at risk of being exposed to potential hazards that can cause health and safety problems, including furniture UMKM at CV Rumah Menyala in Tegalsari Village, Kandeman, Batang. The results of a preliminary survey found that 10 people were interviewed, 6 of whom admitted that they often experienced shortness of breath while working, 5 people experienced pain in the back (musculus ceretal disorder), 2 people experienced visual impairment due to exposure to sawdust dust. Another problem is that the unavailability of occupational disease prevention management means that the hazards and risks in the workplace cannot be controlled. With these problems, we conducted counseling activities using lecture methods and practical assistance to increase knowledge and awareness of the management of CV Rumah Menyala which was attended by 4 people starting by providing educational understanding related to the importance of a healthy and comfortable work environment to carry out work activities and management can be more active in preventing occupational diseases from every potential hazard found in the workplace with the results of recommendations for a safe, healthy production room layout with the arrangement of storage space for tools and raw materials, personal protective equipment and the installation of a dust extractor from the remaining wood cutting furniture and recommendations for its control.